Analisis Potensi Pendapatan Jasa Giro atas Belanja Modal DKI Jakarta - Puspaningtyas, Caecilia; Raymondra, Lukas Surya; Ramadhani, Amira Putri; Ardhani, Naila Fidelya; Siregar, Hilda Octavana (Studi Ekonomi dan Kebijakan Publik, 2025)
Purpose: This study aims to explore the potential of increasing regional revenue through effective cash management of capital expenditures by withholding cash for value-added tax until the due dates on bank accounts. This analysis also compares the projected potential interest revenue with the actual interest income received by the DKI Jakarta Province to assess its contribution to the local revenue. Methodology/approach: This study used quantitative descriptive methods. The data used in this study are secondary data from DKI Jakarta Province’s Statement of Budget Realization in 2019-2023, especially the Capital Expenditure section. This study also uses the annual interest rate from the Central Bank of Indonesia to calculate the potential of interest revenue. The projection tool used in this study is the Compound Annual Growth rate (CAGR) using Microsoft Excel. Results: The results of this study indicate that revenue generated through cash management of capital expenditure has the potential to increase the local government’s revenue; however, its contribution to the interest income section remains relatively insignificant. Conclusion: Increasing the local government’s capital expenditure increases the potential for earning interest income. Limitations: The limitation of this study lies in its focus, which is restricted to exploring the potential of value-added tax related to capital expenditure.  Contribution: This study may provide stakeholders with the information necessary to manage their cash revenue and increase it with interest income, address the gap in the literature on regional revenue diversification strategies, and contribute to the fields of public policy and financial management.